TWO WAREHOUSE INVENTORY MODEL FOR DETERIORATING ITEM WITH EXPONENTIAL DEMAND RATE AND PERMISSIBLE DELAY IN PAYMENT - KALIRAMAN, Naresh Kumar; RAJ, Ritu; CHANDRA, Shalini; CHAUDHARY, Harish (Yugoslav Journal of Operations Research; Vol 27 No 1 (2017), 2016)
A two warehouse inventory model for deteriorating items is considered with exponential demand rate and permissible delay in payment. Shortage is not allowed and deterioration rate is constant. In the model, one warehouse is rented and the other is owned. The rented warehouse is provided with better facility for the stock than the owned warehouse, but is charged more. The objective of this model is to find the best replenishment policies for minimizing the total appropriate inventory cost. A numerical illustration and sensitivity analysis is provided.